Pengaruh Permainan Engklek Terhadap Keterampilan Motorik Kasar Anak Tunagrahita Ringan SLB Putra Jaya Malang - Muhamad Wahid Ramdon; Slamet Raharjo; Dinta Sugiarto (Program Studi Ilmu Keolahragaan, 2023)
Children with special needs experience intellectual delays due to disturbed nerves. Children with mental retardation are one of the children with special needs, which is caused by low intellectual intelligence in general, which causes slow motor development. This study uses a type of pre-experimental research that is used to identify causes and effects by using a one-group pretest-posttest design. The hopscotch game was chosen as the treatment in this study because the hopscotch game is a simple game. The instrument in this study was carried out using the Gross Motor Development Test (TGMD-2) twice, namely during the pretest and posttest. The results of the paired T test obtained a significant value of 0.00 <0.05, which shows that there is a significant effect and shows that (H0) is rejected (H1) is accepted. Playing hopscotch during 18 meetings gave significant results in improving the gross motor skills of children with mild mental retardation. This is because the hopscotch game is dominated by motor skills such as jumping and throwing. The conclusion from this study is that there is a significant effect of giving the hopscotch game treatment on the gross motor skills of mildly mentally retarded children at SLB Putra Jaya Malang.